(untitled) (Journal of Nepal Geological Society, 2013)
Elevated levels of As in groundwater in the floodplain of the Ganges River have been well-documented over the past 15 years. Recent studies have shown that elevated groundwater As occurs even in Kathmandu Valley in Nepal, a tectonic valley well upstream of the floodplain of the Ganges River. Moreover, studies in Kathmandu Valley showed surface water As to be statistically indistinguishable from groundwater As, which led to the fluvial recharge model in which elevated groundwater As results from losing streams (streams that recharge groundwater) with elevated As, which is a consequence of rapid erosion caused by a combination of monsoon climate, tectonic uplift and deforestation. The objective of this study was to further test the fluvial recharge model and other existing models in Pokhara Valley, another tectonic valley in Nepal Himalaya far upstream from the floodplain of the Ganges River. In November 2010 water samples were collected from 20 hand-dug wells (depths 2-18 m), 12 borings (depths 34-220 m), four springs, 16 streams, three lakes and two caves. Arsenic concentrations in all but one of the 57 samples (a stream) exceeded the WHO As Standard (As= 0.01 mg/L). The As concentration of all surface water (geometric mean As = 0.067 mg/L) was statistically indistinguishable (P = 0.43) from that of all groundwater (geometric mean As = 0.086 mg/L), which is consistent with the fluvial recharge model. Groundwater As was uncorrelated with either sulfate or any combination of the transition elements, which is inconsistent with both the reductive-dissolution and sulfide-oxidation models.